И.ЮСУПОВ ҲӘМ ХХ ӘСИРДИҢ 80-ЖЫЛЛАРЫНДАҒЫ ҚАРАҚАЛПАҚ ЛИРИКАСЫ (Лирикада миллий ояныў дәўири идеяларының лирикалық қаҳарман образы арқалы ашып берилиўи мәселелери) - Алламбергенов, К.А.; Дабылов, П.А. (FAN va JAMIYAT, 2016)
The article is devoted to the study of the poetic publicistic works of I.Yusupov, written in the 80-s of the XX-th century. There is a brief review of that period. There have been studied the peculiarities in the description of the bitter truth and creation of lyrical images comparatively with lyrical works of other poets: M.Seytniyazov, T.Sarsenbaev and K.Karimov. On the basis of the analysis the authors show the poetic skill of I.Yusupov.